An Unusual Association: Iliopsoas Bursitis Related to Calcium Pyrophosphate Crystal Arthritis. (15th October 2015) - Di Carlo, Marco; Draghessi, Antonella; Carotti, Marina; Salaffi, Fausto
Abstract : A 71-year-old man with osteoarthritis and chondrocalcinosis came to our observation developing a swelling in the groin region after a recent left colectomy for adenocarcinoma. The imaging techniques revealed the presence of an iliopsoas bursitis in connection with the hip. The synovial fluid analysis detected the presence of calcium pyrophosphate (CPP) crystals and allowed the final and unusual diagnosis of iliopsoas bursitis related to acute CPP crystal hip arthritis.